Industrial Relations and Human Resources Management in Indonesia: The Omnibus Law Impact - Mas’adi, Didik; Widigdo, Aslam Mei Nur (ARE Publisher, 2024)
Objectives: This study explores the impact of the implementation of the Omnibus Law—specifically the employment cluster—on industrial relations management and human resource management (HRM) in Indonesia. Methodology: Employing a qualitative approach, the research integrates semi-structured interviews, literature reviews, and Analytic Network Process (ANP) analysis to identify challenges, solutions, and appropriate implementation strategies. Finding: The findings reveal that the Omnibus Law introduces flexibility in managing industrial relations and HRM but also poses significant challenges, such as shifts in employment patterns, increased tensions between workers and employers, and concerns over worker welfare. Opposition from labor unions centers on issues such as the reduction of labor rights, the removal of limitations on fixed-term contracts, and flexibility that is perceived to disadvantage workers. Based on the analysis, an implementation model is proposed emphasizing sustainable tripartite dialogue, strengthening union capacity, welfare-oriented flexible work policies, and technology-based supervision. Conclusion: This study offers strategic recommendations for fostering harmonious industrial relations and effective HRM within the framework of the Omnibus Law.